Gustave Guiches, his life and works - Light, Eric (1979)
In recent years the name of Gustave Guiches has begun to appear more frequently in the pages of works dedicated to the great writers of the last quarter of the nineteenth century. It seems, therefore, appropriate that the work of this gifted and versatile writer who enjoyed considerable success and esteem in his life-time, should be made better known.